Real world retrospective analysis of luliconazole 1% and salicylic acid 3% as fixed dose combination in the management of hyperkeratotic dermatophytosis in India - Kharkar, R. D.; Dhoot, Dhiraj S.; Deshmukh, Gaurav A.; Barkate, Hanmant (International Journal of Research in Dermatology, 2020)
Background: In recent times, there is increase in prevalence of hyperkeratotic dermatophytosis in India. These hyperkeratotic lesions usually impede the absorption of topical anti-mycotic agent making infection recalcitrant to topical anti-fungal therapy alone. Hence, many times topical keratolytic are used in combination with topical anti-fungal agents which augment the shedding of scales. Methods: To seek for short period therapy in hyperkeratotic dermatophytosis, we conducted multicentre, retrospective data analysis at 61 dermatology clinics to study effectiveness and safety of Luliconazole 1% and Salicylic acid 3% fixed dose combination (FDC) cream for 2 weeks. Results: A data of 191 patients’ were included in this analysis. All patients have received some of the topicals and switched to FDC. Total symptom score of 7.19±1.91 improved to 3.15±1.12 in just 2 weeks (p<0.05). The clinical improvement rate (percentage of ‘marked improvement’ plus ‘moderate improvement’) was 78% after 2 weeks of treatment. Moreover, 5 patients (2.61%) achieved complete clearance. This FDC was found to be safe in 51.83% (n=99) of the patients whereas 37.7% of the patients (n=72) reported it as almost safe. Minor problems with the safety was found in 9.42% of the patients (n=18). Two patients (1.04%) reported it as not safe and thus shifted to another drug. Irritation and burning were reported as most common adverse events (AE). Conclusions: The short combination therapy with luliconazole and salicylic acid as FDC has been found to be effective and safe. It should be a valuable option for hyperkeratotic dermatophytosis for early achievement of clinical cure and better patient compliance.